PERANCANGAN APLIKASI EDUCATION GAME (EDU-GAME) LANGUAGE TRAINING CENTRE (LTC) JAMBI DENGAN 2 (DUA) PILIHAN BAHASA (ENGLISH & JAPANESE): APLIKASI EDUCATION GAME (EDU-GAME) - -, Elzas (LP2M Universitas Nurdin Hamzah, 2019)
Designing educational game applications as fun learning is the first step to achieving enjoyable and quality learning outcomes. In some cases, there has been a decline in interest in learning Japanese and English in a monotonous way, making students, students, and others high. Based on these problems, the researchers made Japanese and English Language Learning Media applications. With one alternative, it is using the Adobe Flash CS3 application. The research method used is a research and development method (Research and Development) that uses research stages of System Requirements, System Analysis and Design. The object of the research is Game-Based Learning Media Development as supporting material. The design material of this learning media application uses the Adobe Flash CS3 application, creating characters by using the Pen-Tablet on the Paint Tool Sai application, and using the Adobe Photoshop CC application to Finalize Images. By designing this application, it is hoped that it can help users to increase their interest in learning Japanese and English to be fun. Key word: Intructional Media, Game, Adobe Flash CS3, Paint Tool Sai, Pen Tablet.